The last last-day-of-summer - Giles, Lamar (2019)
"The Last Last-Day-of-Summer reminds me that all children deserve to exist in magical spaces where their imaginations and familial bonds will them into heroism. Every single child should have the freedom to be one of The Legendary Alstons. And I, for one, am grateful to Giles, and this brilliant story, for that reminder." ?Jason Reynolds, #1 New York Times bestselling and Newbery Honor?winning author of Stuntboy, in the Meantime In the first Legendary Alston Boys mystery from Edgar Award nominee Lamar Giles, two adventurous cousins accidentally freeze time on the last day of summer, and the secrets hidden between the seconds, minutes, and hours aren't quite the endless fun they expected! Otto and Sheed are the local sleuths in their zany Virginia town, masters of unraveling mischief using their unmatched powers of deduction. And as the summer winds down and the first day of school looms, the boys are craving just a little bit more time for fun, even as they bicker over what kind of fun they want to have. That is, until a mysterious man appears with a camera that literally freezes time. Now, with the help of some very strange people and even stranger creatures, Otto and Sheed will have to put aside their differences to save their town?and each other?before time stops for good. And don't miss the Legendary Alston Boys in their next adventures: The Last Mirror on the Left and The Last Chance for Logan County!
Text Difficulty 4
MG/Middle grades (4th-8th)
740
5.2
Electronic reproduction.
Keywords: Juvenile Fiction; African American Fiction; Science Fiction & Fantasy; Electronic books